2010
DOI: 10.1371/journal.pone.0010510
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chemokine-Glycosaminoglycan Interactions in Donor Tissue Reduces Mouse Allograft Vasculopathy and Transplant Rejection

Abstract: BackgroundBinding of chemokines to glycosaminoglycans (GAGs) is classically described as initiating inflammatory cell migration and creating tissue chemokine gradients that direct local leukocyte chemotaxis into damaged or transplanted tissues. While chemokine-receptor binding has been extensively studied during allograft transplantation, effects of glycosaminoglycan (GAG) interactions with chemokines on transplant longevity are less well known. Here we examine the impact of interrupting chemokine-GAG interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…Modified GAGs and metabolizing enzymes, heparanase and chondroitinase, are also variably reported to modify acute kidney damage. We have also found that changes in Ndst1 expression in mouse aortic transplants can reduce plaque growth [11] and more recent work has demonstrated a correlation between changes in HS GAG disaccharide content and reductions in acute rejection in Ndst1-/-donor allograft transplants in mice (Manuscript submitted, unpublished data). What is both fascinating and also supremely frustrating is the fact that one cannot fully predict the functions of HS and other GAGs, such as chondroitin and dermatan sulfate the main connective tissue and glycocalyx GAGs, by a direct correlation to gene expression.…”
mentioning
confidence: 52%
“…Modified GAGs and metabolizing enzymes, heparanase and chondroitinase, are also variably reported to modify acute kidney damage. We have also found that changes in Ndst1 expression in mouse aortic transplants can reduce plaque growth [11] and more recent work has demonstrated a correlation between changes in HS GAG disaccharide content and reductions in acute rejection in Ndst1-/-donor allograft transplants in mice (Manuscript submitted, unpublished data). What is both fascinating and also supremely frustrating is the fact that one cannot fully predict the functions of HS and other GAGs, such as chondroitin and dermatan sulfate the main connective tissue and glycocalyx GAGs, by a direct correlation to gene expression.…”
mentioning
confidence: 52%
“…Harvested arterial sections were processed and stained with hematoxylin and eosin (H & E) or Masson's trichrome stains as previously described [25][26][27][28][29][30][31]33]. Plaque area, was measured by morphometric analysis using an Olympus CCD color video camera attached to an Olympus microscope, and the ImagePro application program calibrated to the microscope objective [26][27][28][29][30][31]33].…”
Section: Morphometric Analysismentioning
confidence: 99%
“…Plaque area, was measured by morphometric analysis using an Olympus CCD color video camera attached to an Olympus microscope, and the ImagePro application program calibrated to the microscope objective [26][27][28][29][30][31]33]. Both the mean total cross-sectional intimal area and the mean intimal thickness after normalized to the medial thickness were calculated for each arterial section.…”
Section: Morphometric Analysismentioning
confidence: 99%
See 2 more Smart Citations